Reflexivity and the Symbolic We-Relation - Gattamorta, Lorenza (Stan Rzeczy, 2017)
This essay considers the features constituting the symbolic We-relation to seek how the reflexive Self can generate changes to the Self, the You, and the We-relation itself. While critically dialoguing with phenomenological and pragmatist social theories, the essay investigates how subjectivity emerges in the interaction with (verbal and non-verbal) symbols and tries to avoid both subjectivism and the relationism.